Using Environmental DNA to Monitor the Reintroduction Success of the Rhine Sculpin (Cottus rhenanus) in a Restored Stream - Hempel, Christopher A.; Peinert, Bianca; Beermann, Arne J.; Elbrecht, Vasco; Macher, Jan-Niklas; Macher, Till-Hendrik; Jacobs, Gunnar; Leese, Florian (Frontiers in Ecology and Evolution, 2020)
Freshwaters face some of the highest rates of species loss, caused by strong human impact. To decrease or even revert this strong impact, ecological restorations are increasingly applied to restore and maintain the natural ecological status of freshwaters. Their ecological status can be determined by assessing the presence of indicator species (e.g., certain fish species), which is called biomonitoring. However, traditional biomonitoring of fish, such as electrofishing, is often challenging and invasive. To augment traditional biomonitoring of fish, the analysis of environmental DNA (eDNA) has recently been proposed as an alternative, sensitive approach. The present study employed this modern approach to monitor the Rhine sculpin (Cottus rhenanus), a fish species that has been reintroduced into a recently restored stream within the Emscher catchment in Germany, in order to validate the success of the applied restorations and to monitor the species’ dispersal. We monitored the dispersal of the Rhine sculpin using replicated 12S end-point nested PCR eDNA surveillance at a fine spatial and temporal scale. In that way, we investigated if eDNA analysis can be applied for freshwater assessments. We also performed traditional electrofishing in one instance to validate our eDNA-based approach. We could track the dispersal of the Rhine sculpin and showed a higher dispersal potential of the species than we assumed. eDNA detection indicated the species’ dispersal across a potential dispersal barrier and showed a steep increase of positive detections once the reintroduced population had established. In contrast to that, false negative eDNA results occurred at early reintroduction stages. Our results show that eDNA detection can be used to confirm and monitor reintroductions and to contribute to the assessment and modeling of the ecological status of streams.